Clarification of Apple Juice Using New Generation Nanocomposite Membranes Fabricated With TiO2 and Al2O3 Nanoparticles - Severcan, Solmaz Sebnem; Uzal, Nigmet; Kahraman, Kevser (Springer, 2019)
To enhance anti-fouling properties of polymeric membranes during apple juice clarification, PSF/PEI (20/2 wt%) ultrafiltration (UF) membranes were modified with TiO2 and Al2O3 nanoparticles using the phase inversion method. Turbid apple juice samples were clarified using cross-flow membrane filtration system. All fabricated nanocomposite UF membranes had higher apple juice flux values than PSF/PEI membrane. Membrane prepared with 0.01% TiO2 (UFT1) had the highest apple juice flux (at steady state, 44.6 L/m(2)h). The FRR (%) value of TiO2 and Al2O3 incorporated UF membranes was between 90.9-94.0% and 79.6-97.6%, respectively, and these FRR values were higher than that of PSF/PEI membrane (UF2, 60.3%). Porosity and hydrophilicity of the UF membranes significantly increased with the addition of nanoparticles and the highest porosity and hydrophilicity was achieved in the 0.01% TiO2 incorporated UF membrane (UFT1) membrane. Higher flux recovery ratio (FRR) and lower relative flux reduction (RFR) values of Al2O3 and TiO2 incorporated nanocomposite membranes, compared with the unmodified membrane, demonstrated the enhancement in the anti-fouling properties of the PSF/PEI membrane. SEM images of the nanocomposite membranes also proved the nanoparticle incorporation to the PSF/PEI matrix. Color, turbidity, total soluble solid, total phenolic content, and antioxidant capacity of the samples using nanocomposite membranes were better than that of clarified using both commercial and unmodified membranes. TiO2 incorporated nanocomposite membranes had superior performance than Al2O3 incorporated nanocomposite membranes and among these membranes, the ones prepared with the addition of 0.01 wt% TiO2 exhibit the best performance in terms of clarification of apple juice.
Kahraman, Kevser/0000-0002-2786-3944
Keywords: Nanocomposite Membrane; TiO2 Nanoparticle; Al2O3 Nanoparticle; Clarification; Apple Juice; TiO2 Nanoparticle; Al2O3 Nanoparticle